Growth of PTCDA Films on Various Substrates Studied by Scanning Tunneling Microscopy and Spectroscopy. Issue 2 (28th January 2019) - Nicoara, Nicoleta; Gómez‐Rodríguez, José M.; Méndez, Javier
Abstract : The application of scanning tunneling microscopy and spectroscopy (STM/STS) to the study of structural and electronic properties of organic/inorganic systems is presented here. The investigation of PTCDA (3, 4, 9, 10, perylene tetracarboxylic dianhydride, C24 O6 H8 ) on semiconductor or metal surfaces by means of STM/STS shows a wide diversity of results indicating a complex behavior of the PTCDA molecules. It has been found that the surface reactivity highly influences the PTCDA adsorption and growth properties. The degree of molecule–surface interaction can lead to randomly chemisorbed molecules on highly reactive substrates, to one‐dimensional row formation on moderately reactive surfaces and well‐ordered overlayers in the case of physisorbed PTCDA molecules on weakly reactive surfaces. Abstract : Scanning tunneling microscopy (STM) is a widely used technique for characterizing molecular layers. This article reviews some representative examples of PTCDA molecular layers grown and measured under ultrahigh vacuum conditions with STM. Results of PTCDA growth on several different substrates, including metals, semiconductors, and two‐dimensional materials, are shown, emphasizing their similarities and differences arising from the variability of the molecule–substrate interaction.